Hubungan Pengetahuan dan Sikap Wanita Usia Subur (WUS) dengan Pemakaian Alat Kontrasepsi - Nirma Lidia Sari (Jurnal Kesehatan Panca Bhakti Lampung, 2019)
Prevention of maternal mortality and illness is the main reason for the need for family planning services. The family planning program aims to meet the community's need for family planning services and reproductive health in order to build quality small families.The objective of this study to find out the correlation between the knowledge and the behavior of fertile-aged woman toward the using of contraception.This study used descriptive correlative method with cross sectional approach. The data used in this study was primary data that were collected using questioner to 100 fertile-aged woman. This study also used proportional random sampling technique. The data was analyzed by chi square as a computer software program and presented in the form of frequent distribution. From the result of this study, it is known that the knowledge of fertile-aged woman over contraception was in less category (12%), the behavior of fertile-aged woman over contraception was in category of unfavorable (43%), and the fertile-aged woman which did not use contraception counted (17%). Between knowledge of fertile-aged woman (WUS) and the usage of contraception statistically had a correlation valued (p<0, 05). Furthermore, between attitude of fertile-aged woman and the using of contraception had relationship valued (p<0,05). This research indicates that there is a significant correlation between fertile aged woman knowledge with their behavior toward the using of contraception.